IMPLEMENTASI SWOT DALAM PENGEMBANGAN USAHA BAGI ANGGOTA KUB SRIKANDI KECAMATAN CEPIRING KABUPATEN KENDAL - Emaya Kurniawati; Wyati Saddewisasi; Sri Yuni Widowati (Magister Manajemen STIE Bank BPD Jateng, 2020)
Kelompok Usaha Bersama Srikandi (Srikandi Join Venture Group) at Cepiring District, in Kendal Regency has been formed more than 5 years ago, consist of several businessman who have different skills in makingand selling their products. Most of the (Kelompok Usaha Bersama) KUB Srikandi members in running their business, apply minimum knowledge in developing their business to meet the needs and condition nowadaysin which similar products that same with KUB Srikandi products are increasing. This study apply thequalitative analysis techniques and SWOT analysis. The research apply qualitative approach and SWOTanalysis trying to know what strategies are used in the business development of KUB Srikandi members. Basedon the IFAS EFAS diagram, it can be concluded that the business carried out by KUB Srikandi members is inthe first quadrant (I), which means that in this position, KUB Srikandi has strong position and has the goodopportunity to develop. The implementation of strategies that can be done is using the Strengths factor thatexist in the business of KUB Srikandi members Where in fact the business that runs by KUB Srikandi membersfacing a great market opportunities, to develop their business in dealing with it, KUB Srikandi members mustoptimize their productivities.